Einfluss einer elektronischen Patientenakte (EPA) auf das Arzt-Patienten-Verhältnis: eine systematische Übersicht der medizinethischen Implikationen = Influence of electronic medical records (EMR) on the physician–patient relationship : a systematic review of the medical and ethical implications - Eckrich, Felicitas; Baudendistel, Ines; Ose, Dominik; Winkler, Eva C. (Ethik in der Medizin, 2016)
BackgroundIn a model project, the implementation of a comprehensive, personal electronic patient record (PEPA) shall not only improve consistency of care, but also realize the right to informational self-determination to the effect that every patient is made administrator of a data-cloud containing all his medical data. A systematic literature review on the topic “electronic health records (EHR)” anticipates possible ethical challenges in connection with the mentioned PEPA. Of the initial 2487 publications, 51 articles were analyzed: 30 empirical studies, 10 medical ethics analyses, and 11 comments.ResultsIn the empirical studies, a more comprehensive medical record was described as an initial effect. The option for access to the EMR by the patient resulted in a better understanding of the needed medical care and thereby higher compliance by the patient. An improvement of the quality of medical care was attributed to prevention of medical errors through the access to records by the patient, a more effective utilization of physician-patient visitations and an improved understanding of the therapeutic concept. Studies also showed a strengthening of the bond of trust in the physician-patient relationship. Concerns were related to data security, possible decline in the personal physician-patient relationship and potential excessive demands on the patient.DiscussionIn an assessment of the EMR, weighing beneficence against patient autonomy plays a major role. Concerns by medical ethics pertaining to a loss of trust or a disturbance of the physician-patient relationship could not be proven empirically. The feared risks to data security were weighed by those affected in favor of the potential benefits of the EMR. Provided that data are protected, the PEPA has the potential to influence the physician-patient relationship positively through participation of the patient. The specific ethical challenges associated with the co-administration of PEPA will be examined in the pilot project.